Nurses' perceptions of medical service robots in negative‐pressure isolated wards and in general wards: A cross‐sectional survey - Jung Hwan Lee; In Ho Han; Jong Hwan Park; Kye‐Hyung Kim; Jaehyun Hwang; Dong Hwan Kim; Jae Il Lee; Kyoung Hyup Nam (Wiley, 2024)
Abstract Aim To evaluate nurses' workload during the coronavirus disease 2019 (COVID‐19) pandemic and to identify their perception of medical serviced robots (MSRs) that may help with or replace the tasks of nurses in negative‐pressure isolated wards and general wards. Design Cross‐sectional survey. Methods A researcher‐made questionnaire was applied that assessed nurses' current workload and their attitudes towards and perceptions of MSRs. A visual analogue scale (VAS) from 1 to 10 was used to assess workload. Perceptions evaluated on a 5‐point Likert scale ranging from one point for 'strongly disagree' to five points for 'strongly agree'. A higher VAS score indicated a higher workload. On the other hands, a higher Likert score indicated a more positive perception and three points was neutral. The questionnaire was conducted on 150 nurses in negative‐pressure isolated wards for the management of COVID‐19 and 150 nurses in general wards. Quota sampling technique was used as sampling technique. Data analysis was performed through independent t‐tests, chi‐square tests and two‐tailed tests. The p‐value <0.05 was interpreted to statistically significant. Results Two hundred eighty‐two participants responded and 142 belonged to the negative‐pressure isolated ward. The overall response rate was 94%, and 94.7% in the negative isolated ward. The mean score ± standard deviation for nursing‐related psychological stress at the current work site was 7.18 ± 1.58 points, and the mean score for physical workload was 7.65 ± 1.48. The need for MSRs was rated as 3.66 ± 0.86 out of 5. Overall, a positive attitude towards MSRs was confirmed, with no difference between ward groups. The overall ratings were 3.14 ± 1.15 for perceived availability and 3.26 ± 1.13 for perceived efficiency. Both nurse groups perceived that MSRs were most available and efficient for monitoring and measurements. Nurses in negative‐pressure isolated wards perceived MSRs more positively than did nurses in general wards regarding setting of alarms (p = 0.003) and delivery of medical devices/materials (p = 0.013). Based on these results, functional development of MSRs associated with monitoring, measurements, setting of alarms and delivery should be prioritized. No patient or public contribution.